173k views
3 votes
Can someone please help me out with this I’ve been stuck on it

-9+6
Simplify the expression

2 Answers

2 votes

Answer:

-3

Explanation:

-9+6

=6-9

=-3

User Jey Geethan
by
5.7k points
5 votes

Answer:

-3

Explanation:

-9+6

- + = -

So this expression will be subtracted.

-9+6 = -3

The answer is negative because greater value has a negative sign....

User Shauntae
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.